Effectiveness of Information Service with Problem Based Learning Model to Improve Self Control of Students in Junior High School. - Raudhatul Jannah; Yarmis Syukur; Netrawati Netrawati (Universitas Negeri Padang, 2019)
Students in learning activities show low self-control behaviors, namely during ongoing learning activities students often carry out activities that are not related to the learning process. Efforts can be made to improve students' self control by carrying out information services with problem based learning model . The research methodology used is quantitative, this type of research is Quasi Experiment with the design of The Non Equivalent Control Group Design. The subjects of this study were class VIII 3 students as an experimental group and class VIII 8 students as a control group at SMP Negeri 13 Padang. The research instrument used was a Likert model scale. Data were analyzed using the Wilcoxon Signed Ranks Test and the Kolmogorov-Smirnov Two Independent Sample test. The results showed that the information service with problem based learning model was effective to improve students' self control.